Technology commercialization factors, frameworks and models - Amadi-Echendu, J. E.; Rasetlola, R. T. (2011 IEEE International Technology Management Conference, 2011)
This paper describes a study of technology commercialization models based on firm-level case studies. A literature review of published examples is supported by data derived from a survey of technology commercialization enthusiasts. The findings suggest that there are two approaches to technology commercialization: (i) a linear approach featuring sequential interactions and linkages, and (ii) a functional approach where activities are not necessarily performed in any predetermined order or chronological sequence but follow the dictates of entrepreneurial flair.